Teknologi Informasi untuk Perpustakaan, Pusat Dokumentasi dan Informasi - Ermawelis Ermawelis (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2018)
Information technology is the application of a knowledge systematically upon practical assignments within an industry. The application of information technology covering in a range of information system both for libraries and documentation and information centers generally is classified in to four main aspects, which are: library housekeeping, information retrieval, general purpose software and library networking. The impact of information technology in general are: if there is no expansion of working vacancies, an employment will occur, if there is no data protection due to transborder data flow, including sensitive information negative impact will occur in economy and culture sectors, copyright will not be backed up, it will be difficult to control the housekeeping of information